Elective Laparoscopic-Assisted Colectomy for Sigmoid Diverticulitis - Neri, Vincenzo (Society of Laparoendoscopic Surgeons, 2006)
OBJECTIVES: The aim of this study was to evaluate the safety and effectiveness of laparoscopic-assisted sigmoid colectomy for diverticulitis and to assess its postoperative advantages. METHODS: From 1999 to 2001, 5 patients were selectively operated on with a laparoscopic-assisted procedure for uncomplicated sigmoid diverticulitis. In the preceding period (September 1997 through December 1998), 4 patients underwent open procedures for the same pathology. The surgical indication with the same criteria was restrictive: at least 2 acute episodes had occurred that were treated with hospital admission and that were separated by an adequate period (2 months) of medical therapy. RESULTS: No conversions of laparoscopy to an open procedure were necessary. Age, sex, weight, morbidity, and mortality were similar between the 2 groups. Operative time was 180 minutes for laparoscopy and 120 minutes for laparotomy. Postoperative resumption of peristalsis was 24 hours versus 4 days, resumption of alimentation was on the second postoperative day versus the fifth postoperative day, and hospital stay was 7 days versus 12 days for laparoscopy and laparotomy, respectively. CONCLUSION: This study shows the feasibility and the advantages of elective laparoscopic-assisted colonic re-section for uncomplicated sigmoid diverticulitis. The advantages of the laparoscopic approach are the lower need for analgesics and the more precocious ambulation, canalization, resumption of alimentation, and the shorter hospital stay.